2018
DOI: 10.1186/s12889-018-5772-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between objectively-measured attributes of the built environment and selected cardiovascular risk factors in a South African urban setting

Abstract: BackgroundEvidence concerning the relationship between objectively-measured attributes of the built environment with cardio-metabolic risk in populations from lower- and middle-income countries is lacking. In this paper, we describe the association between the objectively-measured built environment with body mass index, blood pressure and physical activity in adult South Africans.MethodsThis cross-sectional study included 341 adults aged ≥35 years drawn from the Cape Town arm of the Prospective Urban Rural Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…BE was not associated with the adiposity of women. Previous research has shown that a more activity-supportive BE and a higher level of PA were related to a lower probability of obesity [ 27 , 41 , 42 , 43 , 44 , 45 ]. However, our results were mixed in a different dimension of BE between men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BE was not associated with the adiposity of women. Previous research has shown that a more activity-supportive BE and a higher level of PA were related to a lower probability of obesity [ 27 , 41 , 42 , 43 , 44 , 45 ]. However, our results were mixed in a different dimension of BE between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also confirmed the relationship between BE and BP. With more public places nearby, such as bus stations, subway stations, et cetera, residents may prefer walking or riding bicycles, accumulate more PA, and thus the risk of hypertension may be lower [ 41 , 49 ]. However, residential density was not associated with PA in women according to our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In addition, studies in SA have shown an association between physical activity and attributes of the built environment, including aesthetics such as the presence of trees and attractive sights, proximity to transport hubs, feelings of personal safety and social cohesion, walking and cycling facilities and freedom from litter. [37][38][39][40][41] These built-environmental factors are inequitably distributed and especially lacking in lower socioeconomic areas, and contribute to the high rates of physical inactivity. [37] The cause of the downward trend in the prevalence of physical inactivity for SA needs exploring, especially in the context of rapid urbanisation, increased use of motorised transport and crime, all of which have been shown to be associated with increased prevalence of physical inactivity.…”
Section: Researchmentioning
confidence: 99%
“…Estelle Victoria Lambert , 1 Tracy Kolbe-Alexander, 1,2 Deepti Adlakha, 3 Adewale Oyeyemi, 4 Nana Kwame Anokye, 5 Shifalika Goenka, 6 Patricia Mogrovejo, 7 Deborah Salvo 8…”
Section: Making the Case For 'Physical Activity Security': The 2020 Wmentioning
confidence: 99%